Entrepreneurship Education for Tertiary Institutions in Namibia - Magaisa, Gibbet Murambiwa; Matipira, Lovemore; Chisoro, Licia (Archives of Business Research, 2018)
The main focus of this paper was to explore the main entrepreneurship areas that can be followed in order to achieve the required outcomes for entrepreneurial tertiary institutions in Namibia. Empirical evidence supports the fact that tertiary institution offerings do not meet the expectations of the students. The quantitative research methodology was applied in writing up this paper. The sample size of the paper comprised of 50 respondents.